Construction of Consumer Protection Against Illegal Online Loan Transactions As a Means of IUS Constituendum in Indonesia - Imanuddin, Iman; Anggraeni, RR. Dewi; Fridayani; Susanto (Magister of Law, Faculty of Law, University of Mataram, 2023)
The rise of illegal online loans has caused a lot of harm to consumers. Some argue that the OJK as a regulator in the field of financial services is considered incapable of protecting consumers. The research method, normative juridical approach with laws and regulations analyzed qualitatively. The conclusions obtained are, first, the regulation of consumer legal protection for online loans according to Indonesian law is carried out by applying the principles of transparency, fair treatment, reliability, confidentiality, and security of consumer data/information. Second, legal protection for online loan recipients is carried out preventively through regulation and supervision, as well as providing information and education to the public about the characteristics of illegal online loans. Repressive legal protection can be carried out by imposing administrative, civil, and criminal sanctions. Suggestions that can be conveyed are that the OJK needs to increase stricter supervision of online loan providers and that laws and regulations are needed that are higher than the existing laws and regulations.